2022
DOI: 10.1186/s12891-022-05010-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early complications, outcome, and mortality in Coronavirus Disease 2019 (COVID-19) infection in patients who underwent orthopedic surgery

Abstract: Background A higher mortality and morbidity rate has been reported in COVID-19 patients undergoing surgery. To reduce the morbidity and mortality rate in COVID-19 patients undergoing orthopedic procedures, we aimed to increase the threshold for surgical planning. Methods In a prospective cohort study, COVID-19 patients who underwent elective or emergent orthopedic surgery in three orthopedic surgery centers from February 2020 to September 2020 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Studies that looked at elective and emergent orthopaedic surgical procedures in the presence of COVID-19 infection also found an increased risk of mortality and perioperative adverse events. 1012 In a recent study by Deng et al 8 that compared risks of postoperative complications pre-COVID-19 to peri-COVID-19, early post-COVID-19, and late post-COVID-19 found that patients who were peri-COVID-19 had an increased risk of postoperative complications and patients who were early post-COVID-19 had an increased risk of pneumonia. Similar to previously published studies, this study found an increased risk of postoperative complications in patients undergoing elective surgery, although the risk varied by surgical subspecialty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that looked at elective and emergent orthopaedic surgical procedures in the presence of COVID-19 infection also found an increased risk of mortality and perioperative adverse events. 1012 In a recent study by Deng et al 8 that compared risks of postoperative complications pre-COVID-19 to peri-COVID-19, early post-COVID-19, and late post-COVID-19 found that patients who were peri-COVID-19 had an increased risk of postoperative complications and patients who were early post-COVID-19 had an increased risk of pneumonia. Similar to previously published studies, this study found an increased risk of postoperative complications in patients undergoing elective surgery, although the risk varied by surgical subspecialty.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies of increased risk of postoperative complications in patients who undergo surgical procedures with a concomitant COVID-19 infection. 6,8,[10][11][12] In a study by Doglietto et al, 6 patients with COVID-19 infection undergoing general, vascular, thoracic, orthopaedic, and neurosur-gical procedures were at higher risk of 30-day mortality and pulmonary and thrombotic complications when compared with a matched cohort. Studies that looked at elective and emergent orthopaedic surgical procedures in the presence of COVID-19 infection also found an increased risk of mortality and perioperative adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…This also accords with other earlier studies from Italy 54 and Iran. 55 This can be due to challenges in the identification and management of surgical site infection in COVID-19 patients, and…”
Section: Dovepressmentioning
confidence: 99%
“…In addition, our study is much larger than the study by Zhong et al and has greater power because of this larger sample size. Mohammadpour et al 14 conducted a prospective cohort study of 6,571 patients undergoing elective and emergent orthopaedic procedures between February 2020 and September 2020. They found a 9.3% mortality rate for patients undergoing these procedures.…”
Section: Discussionmentioning
confidence: 99%